Slow wave sleep and 5-HT2 receptor sensitivity in generalised anxiety disorder: a pilot study with ritanserin. - da Roza Davis, J; Sharpley, A; Cowen, P (1992)
Eight patients with generalised anxiety disorder (GAD) and eight matched healthy controls had their polysomnogram measured on two occasions separated by 1 week. On one occasion they received the 5-HT2 receptor antagonist, ritanserin (5 mg orally) and on the other matching placebo. The increase in slow wave sleep produced by ritanserin was the same in GAD patients as in healthy controls. These findings do not support the hypothesis that GAD is associated with a generalised hypersensitivity of brain 5-HT2 receptors; however, the present data cannot exclude the presence of a regionally specific change in this receptor subtype in anxiety disorders.